State-Owned Enterprises’ performance: the roles of public corporate governance codes and political ideology - Pilla, Leonardo Henrique Lima de (2024)
This dissertation presents three independent articles discussing determinants of the financial and social performance of state-owned enterprises (SOEs), particularly focusing on the roles of public corporate governance codes (PCGC) and of incumbents’ political ideology. The first article sheds light on whether PCGCs can induce SOEs to improve financial performance. The study examines the effects of the 2016 Brazilian Law of SOEs (BLS), which is a comprehensive and mandatory PCGC enforceable to SOEs in all government levels (national and subnational). The empirical examination of a 2010-2023 panel of Brazilian listed firms, including 28 SOEs controlled by national and subnational governments, shows that the BLS increased SOEs’ financial performance as measured by return on assets. The second article discusses how incumbents’ political ideology shapes SOEs’ financial performance. The analysis of a 2019–2022 panel of 317 SOEs controlled by 27 subnational governments in Brazil shows that the more right-leaning the incumbent, the greater the SOEs’ financial performance. However, the association of incumbents’ ideologies with SOEs’ financial performance is weaker when right-leaning incumbents’ parties predominantly display non-policy behaviors (e.g., by prioritizing electoral outcomes or office occupation). Lastly, the third article illuminates how state-ownership shapes corporate social performance (CSP). By examining a 12-year panel of 150 Brazilian listed firms, including 41 SOEs, the study empirically demonstrates that state ownership is positively associated with the social dimension of corporate social performance (CSP), but only when the state is the majority shareholder, and thus able to strongly influence SOEs’ goals. Moreover, the more right-leaning is the political ideology of the government, the weaker becomes the moderating effect of majority state ownership. Collectively, the three articles contribute to the literature by providing a multifaceted understanding of important institutional and political factors that shape SOEs’ performance, both regarding its financial and social dimensions. Particularly, the first article corroborates the strand of research showing that PCGCs can mitigate typical SOEs’ agency conflicts, illustrating how the institutional context matter for SOEs’ performance. The second and third articles expand research about the role of political contingencies, such as incumbents’ ideology—a commonly overlooked gap in current research—, on influencing SOEs’ financial and social performance.